Chronic TLR Stimulation Controls NLRP3 Inflammasome Activation through IL-10 Mediated Regulation of NLRP3 Expression and Caspase-8 Activation - Gurung, Prajwal (Sci Rep, 2015)
While the molecular mechanisms promoting activation of the Nod-like Receptor (NLR) family member NLRP3 inflammasome are beginning to be defined, little is known about the mechanisms that regulate the NLRP3 inflammasome. Acute (up to 4 hours) LPS stimulation, followed by ATP is frequently used to activate the NLRP3 inflammasome in macrophages. Interestingly, we observed that the ability of LPS to license NLRP3 is transient, as prolonged (12 to 24 hours) LPS exposure was a relatively ineffective priming stimulus. This suggests that relative to acute LPS, chronic LPS exposure triggers regulatory mechanisms to dampen NLRP3 activation. Transfer of culture supernatants from macrophages stimulated with LPS for 24 hours dramatically reduced ATP- and nigericin-induced NLRP3 inflammasome activation in naïve macrophages. We further identified IL-10 as the secreted inflammasome-tolerizing factor that acts in an autocrine manner to control activation of the NLRP3 inflammasome. Finally, we demonstrated that IL-10 dampens NLRP3 expression to control NLRP3 inflammasome activation and subsequent caspase-8 activation. In conclusion, we have uncovered a mechanism by which chronic, but not acute, LPS exposure induces IL-10 to dampen NLRP3 inflammasome activation to avoid overt inflammation.